(3aGJJfj UdGI (B!! :s (3deGPG jMGaX GdHYV Ydi GdUdGI (B.. (3HjfeG jJQcgG GdcKjQ ? (B: (3JYQa Ydi CSQGQ gDdGA GdPjf bdeG aGJJge UdGI(B/s - (3LeGd, ESdGes ((3GdbGgQI (B:s (3OGQ RMeI cJGH ddfTQ hGdJhRjY,s, 2018)
(3cJGH (B"(3aGJJfj UdGI(B" (3ef JCdja GdcGJH (B"(3ESdGe LeGd(B" (3cJGH ehLg NGUI def dG jUdhf hjJgGhfhf Ydi GdUdGI aj gPG GdcJGH Sha JLO CMSf GdWQb ddehGXHI YdjgG dCffG fYde HCf GdUdGI gj GdSHjd ddSYGOI hGdWeCfjfI(B... (3cJGH aGJJfj UdGI gh GdMd dcd eSde jQZH aj GdehGXHI Ydi GdUdGI, hjJfGhd ajg cd eG jOhQ aj Pgf GdbGQF hCSCdg hGbYjI hCLhHJgG ef GdfGS Yf GdUdGI, hjJfGhd CjVG YOI CbSGe hef HjfgG (B: (3cf UHGMG, hOhGA GdYGOI, hGUWHQ YdjgG, hdG WGbI dc(B.s
(3eQGLYI hENQGL afj (B: (3YeQh hSGde ShGM ; JUeje GdZdGa (B: (3CMeO RQOb(B.s
Keywords: (3hYX hEQTGOs -- (3GdUdGIs